PERILAKU OPORTUNISTIK MANAJERIAL, KEBIJAKAN DIVIDEN, DAN MEDIASI PROFITABILITAS - Mai, Muhamad Umar (Faculty of Economics and Business Universitas Jenderal Soedirman, 2010)
This study aims to examine the influence of managerial opportunistic behavior on dividend policy, either directly or through an intervening variable as a profitability. The population of this research is the manufacturing companies listed in Indonesia Stock Exchange with the observation period starting in 2001 until the year 2007. Data collection method used was purposive sampling, and obtained as many as 154 sample firms. Furthermore, testing of all hypotheses in this study used path analysis through Amos program package 16.0. Results showed that: 1) managerial opportunistic behavior as proxy for business risk (systematic risk) have a positive effect and significant on profitability; 2) profitability and managerial opportunistic behavior with a proxy of debt to asset ratio have a positive influence and significant on dividend policy; and 3 ) profitability does not mediate the relations of causality between managerial opportunistic behavior and dividend policy.